Detection Methods of Nanoparticles Synthesized by Gas-Phase Method: A Review - Zhang, Xiushuo; Zhao, Xiaolong; Li, Hongsheng; Hao, Xiaorui; Xu, Jing; Tian, Jingjing; Wang, Yong (Frontiers in Chemistry, 2022)
The detection of nanoparticles is the basis of the study of synthesis mechanism, active regulation of synthesis process and the study of the nanoparticles properties after synthesis. It is significantly meaningful to academic and engineering. Although there are many relevant detection methods at present, each method has its own advantages and disadvantages, and its measurement quantity and application conditions are also different. There is a lack of unified sorting and generalization. In this paper, the significance of detection of nanoparticles synthesized by gas-phase method is introduced, the development of detection technology is reviewed, and the future is prospected. It is hoped to provide reference for the detection of nanoparticles under various conditions and the development of new detection methods.